Experimental Evaluation of Stability and Rheological Properties of Foam Cement for Oil Wells (Journal of Engineering, 2024)
Oilwell cementing operations are crucial for drilling and completion, preserving the well's productive life. However, weak and permeable formations pose a high risk of cement slurry loss, leading to failure. Lightweight cement, like foamed cement, is used to avoid these difficulties. This study is focused on creating a range of foamed slurry densities and examining the effect of gas concentration on their rheological properties. The foaming agent and foam stabilizer are tested, and the optimal concentration is determined to be 2% and 0.12%, respectively, by the weight of the cement.Furthermore, the construction of samples of foam cement with different densities (0.8, 1.0, 1.2, 1.4, and 1.6) g/cc is performed to find the relation with different volumetric percentage gas in foamed cement slurry (57.5, 47, 36, 25.5, and 15%). The relationship between rheological properties and foam quality is discussed, as the presence of gas plays a significant role in enhancing rheological properties. The rheology of foam cement increases proportionally with increasing foam quality, especially the plastic viscosity, which is 26 cp at 0% foam quality and 50 and 65 cp at 15% and 57.5% foam quality, respectively. Also, yield points increase as foam quality improves. Therefore, it is feasible to exclude certain cement additives that increase viscosity.